Chassis Maintenance and Vehicle Power Transfer Learning: The Effectiveness of STEM on Students' Critical Thinking Ability - Heru, Nur; Wagiran, Wagiran; Daryono, Rihab Wit (Journal of Education Technology, 2021)
The low critical thinking ability of students in the chassis maintenance and power transfer learning so that the required competencies are not achieved. This study aims to analyze critical thinking skills in chassis maintenance and power transfer learning which is taught using the Science, Technology, Engineering, and Mathematical (STEM) learning model and the conventional learning model. This research is a quasi-experimental type of research. The population in this study were students of class XI TKR 1 and XI TKR 2 as many as 69 students. Data collection techniques used documentation technique and test technique. The data analysis technique used descriptive analysis to know the category of students’ critical thinking skills and inferential analysis, including normality, homogeneity, and hypothesis by using a t-test to know the comparison of students’ critical thinking skills in learning chassis maintenance and power transfer which is taught using the Science, Technology, Engineering, And Mathematical (STEM) learning model and conventional learning models. This study shows that descriptive analysis obtained a Mean of 83.49 that was classified into a very high category and very effective category. The t-test proves the data. The tvalue value is 8045, and the ttable is df 67 = 2,000, so it can be decided that H0 is rejected. Ha is accepted because tvalue > ttable, so it can be concluded that the Science, Technology, Engineering, and Mathematical (STEM) learning model is effectively used to improve critical thinking skills compared to using conventional learning models.